Effects of a hybrid delirium nursing competency enhancement program using the metaverse and standardized patients for intensive care unit nurses: a quasi-experimental study - Juwon Yun; Mi Yang Jeon (Journal of Korean Academy of Nursing, 2026)
Purpose: This study evaluated the effects of a hybrid simulation program using the metaverse and standardized patients to enhance delirium nursing competency among intensive care unit (ICU) nurses. Outcomes included delirium nursing knowledge, attitudes, and performance confidence.Methods: A quasi-experimental study with cluster allocation was conducted among 52 ICU nurses, including 28 in the experimental group and 24 in the control group. Data were collected from July 8 to August 28, 2024. The experimental group participated in a hybrid delirium nursing competency simulation program comprising two metaverse-based sessions (lectures, quizzes, discussions, and practice) followed by a face-to-face standardized patient simulation session. The control group received a conventional face-to-face lecture on delirium nursing. Data were analyzed using the chi-square test, the Fisher exact test, the independent t-test, and the paired t-test with IBM SPSS Statistics ver. 27.0.Results: After the intervention, the experimental group demonstrated significantly greater improvement in delirium nursing attitude (t=2.05, p=.046) and performance confidence (t=3.35, p=.002) compared with the control group. However, the change in delirium nursing knowledge did not differ significantly between groups (t=0.71, p=.483).Conclusion: The hybrid delirium nursing competency program using the metaverse and standardized patients was associated with greater positive changes in ICU nurses’ delirium nursing attitudes and performance confidence than conventional lecture-based education. This immersive and interactive hybrid simulation approach may be a sustainable continuing education strategy for strengthening delirium nursing competency among ICU nurses.